Labour and irish political party system - a suggested approach to analysis - Farrell, B (Economic & Social Studies, 1970)
In the politics of the Irish state only three parties have been able to maintain substantial electoral support for more than a decade. Two - Fianna Fail and Fine Gael - stem from the same Sinn Fein party which in the years immediately after 1916 became the vehicle of the Irish independence movement. Their original leaders re-established independent Irish parliamentary institutions in the first Dail of 1919.1 Their participation and disagreement in the subsequent debate on the Anglo-Irish Treaty determined the basic cleavage in the Irish political party system. These leaders and the parties they founded continued to dominate Irish politics for the next fifty years; they were the poles around which two large groupings of opinions, interest and loyalties clustered. The third, the Labour Party, has always played a subsidiary role; its activities, in Professor Chubb's phrase, have 'never seriously impaired the bi-polarism of Irish politics.'
Keywords: Economics; Sociology